The Legal Basis for Non-Monetary Remedies for Violations against Civilians in the International Law - Dr-Osama Yousif Najim; Researcher : Maryam Farhan Darweesh (The college of law and political science journal, 2024)
It is generally accepted that the protection of Human Rights is a fundamental goal of the modern international law. In recent decades, most regional and international organizations have adopted Human Rights standards and responded to human rights violations by granting remedies to the individuals whose rights have been violated in there domestic law, There are many forms of non-monetary remedies mentioned in many United Nations instruments related to human rights, For example the Right to the truth, which can be defined as the right for victims of the gross human rights violations, their families, and the society, to know the truth about what happened to identify those responsible for these violations, Finally to document the circumstances and reasons that led to it. The second form is restitution, which can be defined as restoring the circumstances that existed prior to the violations either by ending the violation or restoring conditions to what they were before the internationally wrongful act occurred. The third form is satisfaction, which can be defined as an acceptable means of redress in cases of reparation for moral damages, For example, guarantees of non-repetition as well as an apology, The fourth form is rehabilitation, which is measures aimed at alleviating the physical, psychological, and the social harm suffered by the victims.In sum, the United Nations General Assembly has confirmed on more than one event, the importance of addressing remedies for victims of violations of the international law in an organized and comprehensive manner at the national and international levels has been emphasized, Therefore many international instruments have been issued that stipulate these remedies, whether at the level of international humanitarian law or at the level of international human rights law, as well as the legislations  at the national level.